High precision X-ray spectroscopy of kaonic neon - F. Sgaramella; D. Sirghi; K. Toho; F. Clozza; L. Abbene; C. Amsler; F. Artibani; M. Bazzi; G. Borghi; D. Bosnar; M. Bragadireanu; A. Buttacavoli; et al. (Physics Letters B)
The high-precision kaonic neon X-ray transitions measurement performed by the SIDDHARTA-2 collaboration at the DAΦNE collider is reported. Both the X-ray energies and yields for high-n transitions were measured, demonstrating the feasibility of sub-eV X-ray spectroscopy for kaonic atoms using low-Z gaseous targets. The measurement provides valuable insights into the de-excitation processes in kaonic atoms, providing new input data for the refinement of the corresponding theoretical models, and a framework for testing Quantum Electrodynamics in strange exotic atoms.